BOOK REVIEW OF AIDIT: DUA WAJAH DIPA NUSANTARA - Pramudhita, Zsazsa Bhaskara (LANTERN (Journal on English Language, Culture and Literature), 2014)
DN Aidit is the most controversial figure in Indonesia’s history. DN Aidit’s name become some kind of taboo to be discussed or talked. After the “New Order” era, DN Aidit’s name begin to be discussed on media again. Many books discussed DN Aidit, one of them is Aidit: Dua Wajah Dipa Nusantara. This book discussed two sides of DN Aidit, DN Aidit’s good side and bad side. This book offers a more complete version of DN Aidit. This final project will discuss and analize about this book.